Character Education Through Social Studies Learning in Elementary Schools - Hasibuan, Erika Fatmasari; Nasution, Nursakinah (Journal of General Education Science, 2024)
The importance of character education is applied in the learning process. The application of character education to the learning process to instill character values in students can be instilled or developed through Social Sciences (IPS) subjects. The social studies learning process takes place with a contextual approach. The aim of this research is to find out character education through elementary school social studies learning. The method used is literature study. The results of the research are that character education can be instilled or developed in students through Social Sciences (IPS) subjects. The implementation of character education certainly goes through various stages in ongoing social studies learning. Education is basically a conscious effort to develop the potential of students. Character education is an effort to shape children's personalities so that they become good human beings, good citizens of society and a good country. So that we can anticipate the symptoms of crisis that the country will face along with developments over time. Social studies education is a subject that studies social life and the material is based on studies of history, geography, economics, sociology, anthropology and state administration. Through social science learning, character education values can be included by integrating the material in social science learning.